(untitled) (Journal of Asian Development Studies, 2024)
Tehsil Babuzai, District Swat, Khyber Pakhtunkhwa, Pakistan, has experienced a fast population increase, substantially influencing land use and land cover (LULC), raising ecological and environmental issues. Thisstudy examines changes in LULC between 2001 and 2020 using US Geological Survey (USGS) satellite images. The paper analyses six primary land cover classes: farmland, built-up area, woodland, water bodies, rangeland, and barren Land using maximum likelihood supervised classification. The findings show a significant rise in rangeland (from 49.1% to 53.7%), built-up areas (from 8.5% to 13.7%), and barren Land (from 5.1% to 11.1%). On the other hand, there is a noticeable decline in the number of water bodies (from 2.1% to 1.6%), agriculture (from 21.2% to 12.2%), and forest cover (from 13.7% to 7.5%). These alterations underscore the detrimental consequences of urban growth on the area’s natural resources, demanding prompt and deliberate planning to protect the ecosystem and guarantee sustainable development. This research is crucial for understanding land use changes’ dynamics and impacts, providing valuable insights for policymakers and urban planners. It highlights the need for sustainable land management practices to mitigate adverse environmental effects and promote balanced regional development